EVALUATION OF HYPERTONIC SALINE SOLUTION IN COMBINATION WITH CEFTIOFUR HCL AND FLUNIXIN MEGLUMINE IN THE TREATMENT OF HAEMORRHAGIC SEPTICAEMIA IN BUFFALOES - M. A. Zafar; G. Muhammad; Z. Iqbal; M. Riaz (Journal of Animal and Plant Sciences, 2012)
This study was undertaken for the evaluation of efficacy of hypertonic saline solution (HSS) in combination with ceftiofur HCl and flunixin meglumine (FM) in haemorrhagic septicaemia in buffaloes. For this purpose, 50 buffaloes suffering from haemorrhagic septicaemia were selected from the field and randomly divided into two equal groups (A and B). Group A served as control and treated with ceftiofur HCl, IM and flunixin meglumine, IV @ 6 and 2 mg/kg BW, respectively. While animals of group B were additionally administered with rapid intravenous infusion of hypertonic saline solution (7.5% NaCl) @ 4 ml/kg BW followed by normal saline solution @ 10 ml/kg BW. Treatments were started after application of cold water on head for 15 minutes. Ceftiofur HCl and flunixin meglumine were repeated after 12, 24 and 48 hours in both the groups. Animals were then monitored for 24 hours after initiation of treatment. Haematological parameters, serum electrolytes and serum biochemical profiles were measured at baseline, 1, 3, 6, 12 and 24 hours after treatment and survival index was recorded at interval of one week. The survival percent was 50 and 80 amongst animals treated respectively with protocol A and B, respectively. In terms of reduction of severity of disease, group B showed significant difference (P < 0.05) over group A. The treatment protocol B exploiting the use of hypertonic saline solution in combination with cephalosporin (ceftiofur HCl) plus a non-steroidal anti-inflammatory drug (flunixin meglumine) was more effective than the conventional treatment i.e. ceftiofur HCl and flunixin meglumine alone for the treatment of haemorrhagic septicaemia. It was concluded from the study that administration of hypertonic saline solution in combination with ceftiofur HCl and flunixin meglumine has beneficial effects in the treatment of haemorrhagic septicaemia in buffaloes.
Keywords: Ceftiofur; flunixin meglunine; Haemorrhagic Septicaemia